Membangun Emosi Positif melalui Promosi Penjualan dan Lingkungan Toko Dampaknya terhadap Impulse Buying - Nindyakirana, Rani Hapsari; Maftukhah, Ida (Universitas Negeri Semarang, 2016)
The purpose of this study is to find out the direct and indirect effects of sales promotions, store environment, and positive emotions as an intervening variable on impulsive buying decisions. Businessman needs to plan a promotion strategy and arrange the store to be more interesting so that the consumers are interested in doing an impulsive buying. The population in this study is all consumers in Clothing Stores Meilleur Ami Semarang that do the impulsive buying. The sampling in this study uses incidental sampling technique with total of 100 respondents. The method of data collection in this study is a questionnaire method. The method of analysis in this study uses path analysis using SPSS 21.0 for Windows.The results of this study show that the sales promotion variable affects the positive emotions of 0,242, the sales promotion affects on impulsive buying amounted to 0.399, store environment affects the positive emotions of 0.374, a store environment affects on impulsive buying amounted to 0.286, the influence of promotion on impulsive buying mediated by positive emotion at 0.491, and the influence of store environment on impulsive buying mediated by positive emotions at 0.428. Therefore, it can be concluded from this study that the sales promotion, store environment, and positive emotions as an intervening variable affect directly and indirectly on impulsive buying. Furthermore, the suggestion for the company is that they should maximize the lighting in the room which is not getting light enough.